The effects of first mating age on average litter size at birth and weaning in rats - Ahmet Nazlıgül (Eurasian Journal of Veterinary Sciences)
The purpose of this experiment was to examine the effect of the lirst mating age on the average litter size at birth and weaning of rats. Thirty female Sprague Dawley rats were used in this study. The ages of animais in the time of first mating were 10 weeks for the first group and 14 weeks for the second group. The experiment was carried out for one year and only the first five births were taken into consideration. Average litter size at birth were 9.42 and 9.45 , and average Sitter size at weaning were 8.41 and 7.95 for the groups, respectively. It was concluded that the first mating age of the rats could be earlier than 2.5 months of age under good management conditions.